Pengadaptasian Budaya Islam terhadap Seni Musik Tarawangsa - Dhafin Gufran; Erik Setiawan (UNISBA Press, 2023)
Abstract. Starting from the researcher's interest in music, especially Tarawangsa, the researcher chose to discuss one of the traditional arts of West Java, namely Tarawangsa Traditional Music, in which there are elements of Islamic cultural adaptation. This art is spread in several areas, one of which is in the Cikondang area, Lumajang, West Java, Cikondang Village is one of the Sundanese traditional settlements that still maintains the value of its traditions and customs, there is one complex that is sacred including traditional houses that are the center of traditional activities, sacred forests, pacilingan, rice fields and sacred tombs. Traditional ceremonies in Cikondang Lamajang Village are often accompanied by tarawangsa performances, even for ceremonial events to Islam, Tarawangsa is often presented. This attracted the attention of researchers to find out the adaptation of Islamic culture to the traditional music art of Tarawangsa, for this reason, the researcher focused on this research problem including; the performance and process of presenting traditional Tarawangsa music as well as the experiences and meanings of the performers, the adaptation of Islamic culture found in traditional tarawangsa music. The purpose of this study is to find out the meaning of the experience of Tarawangsa performers in traditional ceremonial performances, to find out tarawangsa actors interpret the adaptation of Islamic culture in tarawangsa performing arts. This research uses qualitative methods with the phenomenological approach of Alfred Schutz. The data collection technique is by field observations in Ci Kondang village, as well as in-depth interviews with Bah Ayi and tarawangsa art practitioners, as well as documentation. The result of the research that has been done is that the performance and presentation process of traditional tarawangsa music is carried out in accordance with what has been done by previous generations. The Islamic value that dominates more in traditional tarawangsa music is the value of Aqidah (faith). Where the value of this faith becomes a real form in the daily lives of players and connoisseurs such as by saying dhikr sentences, as well as practicing Allah's commandment, which is to be grateful. Abstrak. Berawal dari ketertarikan peneliti terhadap seni musik khususnya Tarawangsa maka peneliti memilih membahas salah satu kesenian tradisional Jawa Barat yaitu Musik Tradisional Tarawangsa yang didalamnya terdapat unsur adaptasi budaya Islam. Kesenian ini tersebar di beberapa wilayah salah satunya di daerah Cikondang, Lumajang, Jawa Barat Kampung Cikondang merupakan salah satu pemukiman adat sunda yang masih menjaga nilai nilai tradisi dan adat-istiadatnya, terdapat satu komplek yang di keramatkan diantaranya rumah adat yang menjadi pusat kegiatan adat, hutan keramat, pacilingan, sawah dan makam keramat. Upacara adat di Cikondang Desa Lamajang sering diiringi oleh penampilan Tarawangsa, bahkan untuk acara-acara upacara ke agama Islam pun sering kali Tarawangsa dihadirkan. Hal tersebut menarik perhatian peneliti untuk mengetahui adaptasi budaya Islam pada kesenian musik tradisional Tarawangsa, untuk itu peneliti memfokuskan permasalahan penelitian ini meliputi; penampilan dan proses penyajian musik tradisional Tarawangsa serta pengalaman dan makna dari para pelaku, pengadaptasian budaya Islam yang terdapat pada musik tradisional tarawangsa. Tujun dari penelitian ini ialah untuk mengetahui makna pengalaman pelaku seni Tarawangsa dalam pertunjukan upacara adat, untuk mengetahui pelaku Tarawangsa memaknai pengadaptasian budaya Islam dalam seni pertunjukan Tarawangsa. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi Alfred Schutz. Adapun teknik pengumpulan datanya yaitu dengan observasi lapangan di desa Ci Kondang, juga wawancara mendalam dengan Bah Ayi dan para pelaku kesenian tarawangsa, serta dokumentasi. Hasil dari penelitian yang telah dilakukan ialah Penampilan dan proses penyajian musik tradisional tarawangsa dilaksanakan sesuai dengan apa yang telah dilakukan oleh generasi sebelumnya. Nilai Islam yang lebih mendominasi pada musik tradisional tarawangsa ini adalah Nilai Aqidah (keimanan). Yang dimana nilai keimanan ini menjadi bentuk nyata dalam kehidupan sehari-hari para pemain maupun penikmatnya seperti dengan mengucapkan kalimat dzikir, juga mengamalkan perintah Allah yaitu bersyukur.